Patient decision aids and outcomes of its performance into routine clinical settings: A review article - Mousavizadeh, Seyedeh Narjes; Ilkhani, Mahnaz (Advances in Nursing & Midwifery, 2016)
Abstract: Background and aim: One of the basic principle of patient protection is the patient’s right to make decisions for their health. Over two decades, results of the studies have showed the positive effects of patient participation in decisions about their treatment and application of "patient decision aid". But so far, the impact of implementing of these interventions in routine practice in clinical settings, is not clear. The aim of this study was to analyze the findings of published studies that investigated the effectiveness of strategies, methods or approaches to implement IDES into routine clinical settings. Materials and methods: This is a review article. Electronic resources and databases such as CINAHL, Embase, Medline, Scopus, Science Direct, MD Consult, OVID and Google Scholar were searched to find all studies that have investigated various aspects of the subject of "patient decision aids". Findings: There are significant challenges to the implementation of patient decision support. The study results showed indifference and noncooperation between health professionals. The noncooperation was stemmed in lack of confidence in the content of IDEs and concerns about disruption of workflows. Conclusion: It is too soon to make firm recommendations about the best way of implementation of patient decision support methods into routine practice. Because teams that use this model consistently report difficulties. It seems that the major problems against the use of these interventions are their limit implementation and they need further and special investigation. Keywords: Decision-Making; Decision Support Techniques; Patient Outcome Assessment